USE OF PERSONAL PROTECTIVE EQUIPMENT (PPE) AND EVENTS PHLEBITIS - Herawati, Cucu; Andreani, Novi; Kristanti, Iin; Seventina Sirait, Healthy; Indragiri, Suzana; Tri Wahyuni, Nuniek; Nurjannah Yulistiyana, Laili (Jurnal Kesehatan Kusuma Husada, 2025)
There are still many incidents of infection phlebitis during the home care process. Sick to patients and staff p This describes quality service. House less pain​. Incident phlebitis is caused by one of the reasons for not using PPE by the standard. Research purposes: To analyze the level of compliance with the use of PPE in nurses who have had incidents of phlebitis in the Hospital. Types of research This analytic design uses a cross-sectional method. Population in the study: There were 108 nurses in the Hospital and 52 samples. The sampling technique uses simple random sampling. Data collection methods are interviews and observations. The cross-tabulation results showed that respondents who complied with the use of PPE were 20 (38.5%), and respondents who did not adhere to the use of PPE were 8 (15.4%). Obtained P value = 0.001, there is a connection between compliance with the use of PPE in nurses and incident Phlebitis in the Hospital. Expected Hospitals carry out socialization about the routine use of PPE and monitor evaluations once a month regarding the implementation of compliance with the use of PPE; health workers should be obedient in using PPE and carry out work per existing standard operational procedures.